Expression patterns of OCT-4 and NANOG genes in buffalo (Bubalus bubalis) embryos produced by in vitro fertilization or parthenogenetic activation - Kumar, D; Anand, T; Shah, R A; Singh, M K; Chauhan, M S; Manik, R S (The Indian Journal of Animal Sciences, 2012)
The correct gene expression in early cleavage stage embryos is essential to sustain embryo development. The precise regulation of genes involved in pluripotency like OCT-4 and NANOG is crucial to the formation of inner cell mass and trophoblast cells. Therefore, the present study was focused on the expression of OCT-4 and NANOG genes in buffalo embryos produced by in vitro fertilization (IVF) or parthenogenetic activation (PA). For gene expression studies, a group of 5 embryos at every developmental stage of 2-cell-, 4-cell-, 8-to 16– cell, morula and blastocyst generated through IVF and PA were collected on second, third, fourth, fifth, and seventh or eighth day post-insemination or activation respectively. The transcripts of OCT-4 were detected in embryos at all the stages examined, starting from the 2-cell stage through the hatched blastocyst stage in both IVF and PA embryos. Whereas, the expression of NANOG was observed to begin at the morula stage and was also present in the blastocysts stage of embryos produced through either protocol. These results indicated that OCT-4 and NANOG used as a marker for pluripotency of ESCs in several species are expressed in early stage of buffalo embryos and continue to be expressed in blastocysts stage.